Psychological well-being of a school teacher: predictors and correlations of the PERMA model - E.N. Volkova (Психологическая наука и образование)
Context and relevance. The PERMA model is basic for understanding what elements and their corresponding psychological mechanisms determine a teacher's positive functioning. Objective. The aim of the study is to identify the characteristics of psychological well-being of Russian teachers and to determine its social and demographic predictors and correlates. The predictors are age, gender, length of service, qualification category, his/her place of residence and region of residence, family status and the presence of his/her own children. The correlates of teacher's psychological well-being are teacher's attitude to school, motivation, energy, enthusiasm, satisfaction with work, relationships with colleagues, involvement in school life, self-assessment of effectiveness, professional achievements. An additional goal is to determine norms of psychological well-being for Russian teachers based on the PERMA-profiler instrument. Methods and materials. The volume of the aggregate sample amounted to 1018 people – secondary school teachers, 884 people (86,8%) are women, 134 people (13,2%) are men. Results. The Russian teachers have the same level of psychological well-being as a whole Russian sample. However, teachers are more involved in activities, there is an imbalance of negative/positive affect, positive assessments of their physical health are reduced. The component of relationships is not characterized by significant expression, which can be a limitation in the productive and effective performance of professional activities. Predictors of school teacher psychological well-being are older age, presence of family and children, as well as living in regions remote from the center, with lower population density and having national autonomies in their composition. The psychological well-being of a teacher is associated with the development of autonomous motivation, energy, enthusiasm, involvement in work, agency, high evaluation of self-efficacy. Characteristics of the school’s organizational climate and organizational culture are related to the teacher’ psychological well-being.